Penentuan Jumlah Kendaraan Transjogja Dengan Metode Simulasi - Masrul Indrayana (Jurnal Optimasi Sistem Industri, 2010)
Improving the public service, Yogyakarta city government formally operate a new transportation system "transjogja" The trial results using transjogja produce different responses from the public. Some passengers complained about the time interval between the arrival of a very old bus. Interarrival time of buses at a bus stop is badly affected by the path length and number of stops that serve the fleet. It is also closely related to factor profitable and density / number of passengers in the bus stop / path. It required a study to determine the number of bus fleet for each path without increasing the risk and investment failures. The assessment can be done with the help of simulation methodology. Based on these studies have been done on Route 2B and assistance Arena Software, acquired three service models to choose from a fleet of 4 units per hour with maximum queuing time of 7.6196 minutes, 3 units of the fleet per hour with a maximum queuing time of 10.4605 and 2 units fleet per hour with maximum queuing time of 17.1047.